Дослідження на фізичній моделі впливу величини кута розкриття випускних отворів занурених стаканів на характер витікання сталі у кристалізаторі машини безперервного лиття заготовок (МБЛЗ) - Верзілов, О.П.; Горшкова, А.А.; Смірнов, Ю.О.; Верзілова, А.Р. (Physico-technological Institute of Metals and Alloys, 2023)
When designing the submerged entry nozzle (SEN) for the conditions of a particular metallurgical production, special attention is paid to the shape and angle of opening of the side holes. The shape of the outlet holes determines the mass flow rate of steel and the shape of the jet, and the opening angle of the side holes determines the angle of flow of the metal jet and the whole pattern of movement of the metal flows in the mold, number and direction of the circulation flows. As a result of the research, it was revealed the influence of the opening angle of the outlet holes of the SEN on the nature of the flow inside the mold and established the optimum opening angle of its side openings. The processes of metal outflow in the mold of slab continuous casting machines (CCM) were studied on the physical model while changing the opening angle of the side holes of the SEN in the range from -20° to 20° with a step of 5°. In this case, it was noted the existence of two fundamentally different patterns of metal outflow in the mold, which are characterized by one or two circulation zones. The change in one-circulation pattern to a two-circulation one is observed in the range from -10° to -5°. It was established, that the rational value of the angle of opening of the side holes of the SEN is 10–15°, which can be used for casting slabs of various widths up to 1500–1600 mm. When choosing the optimal opening angle of the SEN, a correction towards decreasing the opening angle (about 5–8°) can be recommended, which takes into account that the jet outflow angle during casting is greater than the nominal opening angle, as it is influenced by upper circulation flows. The width of the mold largely determines the choice of the opening angle of the side holes of the SEN. Therefore, for slabs of small width, the use of SEN with a disclosure angle from -20° to 5° is irrational, due to the interaction of the flows flowing out of the SEN with a solid metal crust, which is crystallized on the walls of the mold. At the same time for slabs with a width of 1500 mm the opening angle in the range from -5° to 5° provides optimal conditions for the movement of flows in the mold, oscillations on the meniscus, as well as solidification of the solid crust on the narrow walls of the mold.